Hypergravity resistance exercise: the use of artificial gravity as potential countermeasure to microgravity - Yang, Yifan; Baker, Michael; Graf, Scott; Larson, Jennifer; Caiozzo, Vincent J (Journal of applied physiology (1985), 2007)
Departments of 1 Orthopedic Surgery and of 2 Physiology and Biophysics and 3 General Clinical Research Center, School of Medicine, University of California, Irvine, California Submitted 16 July 2007 ; accepted in final form 13 September 2007 The aims of this study were to 1 ) determine if hypergravity (HG) squats can produce foot forces similar to those measured during 10-repetition maximum (10RM) squats using weights under normal 1-G z condition, and 2 ) compare the kinematics (duration and goniometry) and EMG activities of selected joints and muscles between 10RM and HG squats of similar total foot forces. Eight men and six women [27 yr (SD 4), 66 kg (SD 10)] completed ten 10RM [83 kg (SD 23)] and 10 HG squats (2.25–3.75 G z ). HG squats were performed on a human-powered short-arm centrifuge. Foot forces were measured using insole force sensors. Hip, knee, and ankle angles were measured using electrogoniometers. EMG activities of the erector spinae, biceps femoris, rectus femoris, and gastrocnemius were also recorded during both squats. All subjects were able to achieve similar or higher average total foot forces during HG squats compared with those obtained during 10RM squats. There were no differences in total duration per set, average duration per repetition, and goniometry and EMG activities of the selected joints and muscles, respectively, between 10RM and HG squats. These results demonstrate that HG squats can produce very high foot forces that are comparable to those produced during 10RM squats at 1 G z . In addition, the technique and muscle activation are similar between the two types of squats. This observation supports the view that HG resistance training may represent an important countermeasure to microgravity. Space Cycle; squats; space; spaceflight; human centrifuge Address for reprint requests and other correspondence: V. J. Caiozzo, Medical Sciences I B-152, Dept. of Orthopedic Surgery, School of Medicine, Univ. of California-Irvine, Irvine, CA 92697 (e-mail: vjcaiozzatuci.edu )